Environmental Factors and Trust in Taxpayer Compliance Among MSMEs: Faktor Lingkungan dan Kepercayaan dalam Kepatuhan Pajak MSME - Aliyah, Fitri Dwi; Ernandi, Herman (Indonesian Journal of Law and Economics Review, 2024)
Background: Taxpayer compliance is crucial for timely tax reporting, with e-Filling provided by the Directorate General of Taxes (DJP) facilitating this process. Specific Background: Trust in government and environmental factors are believed to influence compliance. Knowledge Gap: However, there is limited empirical evidence regarding their interactions, especially the environment's moderating role. Aims: This study investigates the effects of e-Filling implementation and government trust on taxpayer compliance, focusing on environmental moderation. Results: Analyzing a population of boarding house owners with at least ten rooms, results show that both e-Filling and government trust positively affect compliance, while the environment moderates the relationship between e-Filling and compliance but not the effect of government trust. Novelty: This research offers new insights into the interplay between digital tax reporting and environmental factors. Implications: Findings suggest that while technology enhances compliance, the environmental context may also significantly impact taxpayer behavior, indicating a need for tailored compliance strategies. Highlights : E-Filling positively impacts taxpayer compliance. Government trust significantly influences compliance levels. Environmental factors moderate the relationship between e-Filling and compliance. Keywords: Taxpayer, Compliance, E-Filling, Trust, Environment